The Future of Underwater Technology: Challenges and Opportunities for Indonesia in the Global Ocean Economy - Sukri Ramadhan (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2026)
As the world's largest archipelagic nation, Indonesia possesses immense potencial within the global ocean economy. However, mastery of underwater technology is still dominated by developed nations. This perspective article discusses the urgency of developing underwater technology in Indonesia, particularly in the energy, communications, and maritime security sectors. Furthermore, it highlights the challenges of dependency on imported technology, the importance of strengthening human resources (HR), and strategic directions for marine research and innovation policies. The author argues that without an integrated national strategy, Indonesia risks becoming merely a technology market. Conversely, through research investment, industry-academic collaboraon, and blue economy policies, Indonesia has the opportunity to become a signiﬁcant player in the global subsea technology industry.